CSC536: Multimedia Instructional Design / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics And Media (Universiti Teknologi MARA (UiTM), 2022)
This course introduces the instructional design process and model. It emphasizes the importance of instructional design in multimedia learning application. The principles and guidelines in developing an instructional material is studied and applied to the learning application. The concepts and designs associated with ID and learning are emphasized.